Chemotherapic extravasation: the nurse's role in oncological emergency (Research, Society and Development, 2020)
The extravasation of antineoplastic chemotherapy drugs in the peripheral route, results from negligent or accidental actions during the administration of chemotherapy. The present study aimed to review the scientific production aimed at the nurse's performance in the management and prevention of the extravasation of chemotherapeutic agents, through an integrative literature review, in the Scielo and VHL databases, between the years 2008 to 2020, using the combination of the following terms: nursing and chemotherapy; extravasation of chemotherapeutic drugs; oncological nursing; oncological emergency. 778 articles were obtained, of which 19 (2.44%) were selected, which point out that nurses have limited information about the risks that involve the handling, administration and disposal of antineoplastic agents, as well as the procedures after extravasation. We observed that nurses who work in the oncology field need scientific improvement and adequate training to perform the activities of the sector, in order to minimize the risks of leakage and improve the care provided to the patient.